Patterns of oral hygiene behaviors, daily habits, and caries prevalence in India and dominican republic: A comparative study - Payal Kahar (Wolters Kluwer Medknow Publications, 2019)
Background: The purpose of the study was to gain integrative knowledge on oral hygiene behaviors and daily habits affecting caries experience among rural people in India and Dominican Republic (DR). Materials and Methods: Participants were recruited in two countries: La Esquina community, Province Maria Trinidad Sanchez in DR and in Ramgarh, district Chhindwara in the state of Madhya Pradesh in India. A total of 104 participants (18-80 years) were in the DR sample while 202 participants (18-85 years) were in the Indian sample. Face-to-face interviews collected information on oral hygiene behaviors, daily habits, and dental care. The caries experience was quantified using decayed, missing, and filled teeth (DMFT) index. Results: There were significant differences in a few oral hygiene behaviors, daily habits, and levels of caries experience between the Dominican and Indian subgroups. Use of toothbrush (χ2 = 65.2; P < 0.001), self-reported use of fluoridated toothpaste (χ2 = 94.04; P < 0.001), use of tobacco (χ2 = 32.4; P < 0.001), dental visit (χ2 = 24.84; P < 0.001), attitude toward seeking professional dental care (χ2 = 85.07; P < 0.001), and DMFT scores (F = 13.3; P < 0.001) were significantly different between the two countries. The caries experience was higher in the Dominicans (9.6 ± 8.0 vs. 4.0 ± 5.7) than India's rural. Conclusions: Oral health practices varied considerably between rural populations in these two countries. Caries prevalence was significantly higher in Dominicans despite higher consumption of tobacco and lesser use of toothbrush among rural Indians in the subcontinent.